Factors influencing growth hormone therapy effect during the prepubertal period in small for gestational age children without catch-up growth - Chang Dae Kum; Jung Gi Rho; Hong Kyu Park; Hae Sang Lee; Jin Soon Hwang (Korean Society of Pediatric Endocrinology, 2021)
Purpose Because small for gestational age (SGA) children who fail to experience catch-up growth have an increased risk of short stature in adulthood, growth hormone (GH) treatment is recommended for effective growth. In this study, we evaluated the effect of GH treatment during the prepubertal period and analyzed for correlation between GH treatment response and clinical factors in SGA children. Methods A retrospective, single-center study was conducted from 2014 to 2020. A total of 34 prepubertal children of short stature up to 4 years of age and born as SGA were enrolled. We recorded clinical data including birth data, age, weight, height, bone age (BA), and insulin-like growth factor 1 (IGF-1) levels. Results The mean gestational age and birth weight were 37.50±2.51 weeks and 2,200.00±546.79 g. At the start of GH treatment, the mean chronological age and BA were 5.54±1.73 years and 4.52±1.85 years, respectively. The height standard deviation score (SDS) (-2.47±0.45) and IGF-1 SDS (0.16±1.57) were calculated. Height velocity was 9.43±1.40 cm during the first GH treatment year and 7.63±1.16 cm during the second year (P<0.05). The treatment growth response was positively correlated with young age (P=0.047) and lower BA (P=0.049) at the start of treatment. In multiple regression analysis, IGF-1 SDS change had a significantly positive association with GH treatment response (P=0.045). Conclusions GH treatment is effective for short stature SGA children who do not experience catch-up growth. Early initiation of GH treatment improved growth outcomes. As IGF-1 SDS is positively correlated with height SDS, IGF-1 monitoring is important during GH treatment of SGA prepubertal children.